Development and Evaluation of the Eetmaatje Measuring Cup for Rice and Pasta as an Intervention to Reduce Food Waste - van Dooren, Corné; Mensink, Frederike; Eversteijn, Kim; Schrijnen, Marjolijn (Frontiers in Nutrition, 2020)
Of all stages in the supply chain, more food waste comes from households than any other sector. Dutch composition analysis showed that solid food waste (including sauces, fats and dairy products) via household waste amounted to 48.0 kg per person, per year (in 2013), of which 5.0 kg consisted of cooked rice and pasta. These two product groups were number 1 and 3 in relative waste: 34% of the purchased quantity of rice and 23% of pasta was wasted. Using questionnaires, we discovered that Dutch consumers mainly throw away food because they prepare too much of it. The same is true for rice and pasta because they increase largely in volume when cooked. The water uptake ratio of rice is 2.5 and for pasta 1.8, which increase the chances of consumers overestimating portions. In 2013, more than half of the people did not measure pasta and rice portions. In view of this, the Netherlands Nutrition Centre developed a measuring cup called the Eetmaatje, which uses the recommended volumes for Dutch adults for different types of pasta and rice in dry weight. The theoretical reduction of food waste the Eetmaatje provides is calculated as approximately 6% for pasta and 21% for rice or 12.5% combined. Between 2014 and 2018, more than 1.6 million Eetmaatje cups were distributed for free among Dutch households. Most people in a panel of consumers who own an Eetmaatje (85–89%) think it is handy or very handy to use. A majority of those in the panel (50%–80%) say they use the Eetmaatje most times when preparing a meal. Four out of five of those in the panel (77%–87%) are convinced that the Eetmaatje helps them waste less pasta and rice. Consumers who measure their pasta using the Eetmaatje self-reported that they produced less total food waste. The measured household waste of cooked rice and pasta seems to show a downward trend since the introduction of the cup. There is strong evidence that the Eetmaatje has increased the number of Dutch households measuring rice and pasta and thereby reducing food waste.